2011
DOI: 10.1016/j.aprim.2009.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Factores asociados a reingresos hospitalarios en pacientes de edad avanzada

Abstract: Hospital readmissions have been associated to patient medical condition and to factors related to the health care received. Integrating information from hospital and primary care administrative data bases improves the capacity to identify factors associated with a higher readmission risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 18 publications
0
2
0
2
Order By: Relevance
“…In addition, we have observed that 22.5% of adults with DS in the present study had been admitted at least once during the 12 months leading to the index hospitalisation, with a mortality rate at readmission of 25.2%. The reported rates of readmission among the general population in Spain vary widely, from 16% to 34%, with an associated mortality rate of 7.2% (Alonso Martínez et al, 1998; Martín Martínez et al, 2011). Therefore, mortality during readmission among persons with DS is more than 3‐fold greater than that of the general population.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have observed that 22.5% of adults with DS in the present study had been admitted at least once during the 12 months leading to the index hospitalisation, with a mortality rate at readmission of 25.2%. The reported rates of readmission among the general population in Spain vary widely, from 16% to 34%, with an associated mortality rate of 7.2% (Alonso Martínez et al, 1998; Martín Martínez et al, 2011). Therefore, mortality during readmission among persons with DS is more than 3‐fold greater than that of the general population.…”
Section: Discussionmentioning
confidence: 99%
“…This last feature is not always present in other models, such as the model proposed by Maleki et al [49], which consists of only four questions, including some that are posed directly to the patient/caregiver, such as "does the patient need help with using general transport? "; the Hippisley-Cox and Coupland model [23], with 30 variables, including information not systematically collected in medical records, such as "alcohol status", "smoking status" and "ethnicity"; and the model developed in Spain by Martínez et al [50] that includes the variable "mean nursing care pressure of the primary care team" and "Charlson index" that each require a previous calculation. Other models are more complex and include more variables, as they try to detect the risk of short-term hospital re-admission within, for example, 30 days of discharge, such as PARR-30 [51].…”
Section: Discussionmentioning
confidence: 99%
“…In view of this, the diagnosis of infectious diseases constitutes a problem in that limited medical care is available (e.g. areas with difficult access or rural areas), since these patients require special care due to the complexity of clinical management [7], [10]. This is reflected in an increase in the mortality rate of patients due to delays in treatment [8], [11].…”
Section: Introductionmentioning
confidence: 99%